2013
DOI: 10.1186/1749-8090-8-233
|View full text |Cite
|
Sign up to set email alerts
|

Successful bridge to recovery using two-stage HeartWare LVAD explantation approach after embolic stroke

Abstract: A two-stage explantation of a left ventricular assist device (LVAD) was performed on 47 year old afro-american gentlemen with non-ischemic dilated cardiomyopathy (DCM) who was successfully bridged to recovery. After he suffered a stroke caused by a VAD thrombosis with embolisation, the VAD outflow graft was first ligated using minimally-invasive approach. Two months later, the device was explanted and a manufactured titanium plug was placed into the sewing ring. This stepwise procedure might be beneficial in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The access midline sternotomy is the first method used for the explantation of intracorporeal LVADs. [4] Although full sternotomy LVAD explantation is shown to be feasible, it may be associated with an increased risk for intraoperative bleeding, need for blood transfusions, and postoperative ventricular dysfunction. [5] Cheung et al [6] described a successful subxiphoidal explantation procedure for a HeartMate II, whereas Schweiger et al [5] showed the left lateral thoracotomy without the need for cardiopulmonary bypass (CPB) explantation of the HeartWare LVAD and closure of the apical cannulation site with a titanium plug.…”
Section: Discussionmentioning
confidence: 99%
“…The access midline sternotomy is the first method used for the explantation of intracorporeal LVADs. [4] Although full sternotomy LVAD explantation is shown to be feasible, it may be associated with an increased risk for intraoperative bleeding, need for blood transfusions, and postoperative ventricular dysfunction. [5] Cheung et al [6] described a successful subxiphoidal explantation procedure for a HeartMate II, whereas Schweiger et al [5] showed the left lateral thoracotomy without the need for cardiopulmonary bypass (CPB) explantation of the HeartWare LVAD and closure of the apical cannulation site with a titanium plug.…”
Section: Discussionmentioning
confidence: 99%